Four Blade Grass Chopper Machine Produces Highest Cutting Capacity: Mesin Pemotong Rumput Empat Pisau Memiliki Kapasitas Pemotongan Tertinggi - Virdo Vireta Yudha A.P; Edi Widodo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Grass chopper machines are widely used in livestock farming to support feed preparation and reduce manual labor requirements. Specific Background: Elephant grass is commonly utilized as the primary feed for cattle; however, many farmers still apply conventional cutting methods that require more time and labor. Knowledge Gap: Previous practices have not sufficiently examined the relationship between blade quantity and machine cutting capacity in grass chopper systems operating at different rotational speeds. Aims: This study aimed to design a grass chopper machine and evaluate the performance of blade variations on cutting capacity and fuel consumption. Results: Experimental testing was conducted using 2, 3, and 4 blades at rotational speeds of 1900 RPM, 2500 RPM, and 3000 RPM. The machine using 4 blades at 3000 RPM produced the highest cutting capacity of 5.845 kg/minute with fuel consumption of 88.5 ml/minute, while the 3-blade configuration produced 4.370 kg/minute and the 2-blade configuration produced 3.121 kg/minute. Novelty: The study presents a grass chopper machine design with interchangeable blade variations to compare cutting performance and fuel consumption under identical operational conditions. Implications: The proposed machine can support livestock farmers by providing faster grass chopping processes, reducing labor demands, and increasing feed preparation capacity for cattle farming operations.HIghlights: Four cutting blades generated the largest grass chopping output at 3000 RPM. Fuel consumption increased consistently with higher rotational speed settings. Shorter chopping dimensions were produced by configurations using additional blades. Keywords: Grass Chopper Machine; Blade Variation; Cutting Capacity; Livestock Feed; Mechanical Design